Can We Measure Universities’ Impact on Climate Change? - McCowan, Tristan (International Higher Education, 2022)
Universities have a growing interest in understanding the impact that they have on climate change, whether positive or negative. Yet beyond the direct emissions from their campuses, is it possible to measure their multiple influences through education, knowledge production, and public engagement? This article argues that while it is important to monitor carefully those activities that can be measured, universities should not dismiss those activities that cannot.